Direct Instruction in Inclusive Islamic Education: Enhancing Prayer Memorization among Students with Mild Intellectual Disabilities - Salasiah, Salasiah; Khosiin, Khamam; Benny Prasetya; Syahrin, Muhmammad Alfi (Yayasan Adra Karima Hubbi, 2026)
Background. Inclusive Islamic education faces challenges in supporting students with mild intellectual disabilities, particularly in memorizing prayer recitations that require sequential recall, accurate pronunciation, and sustained attention. Cognitive limitations often reduce students’ independence in performing religious practices, highlighting the need for adaptive instructional strategies. Purpose. This study examines the use of Direct Instruction in inclusive Islamic education and analyzes its role in improving prayer memorization among students with mild intellectual disabilities. Method. A qualitative descriptive case study was conducted using passive classroom observation, in-depth interviews with teachers, school leaders, special education assistants, parents, and students, as well as document analysis. Data were analyzed through an interactive process of data condensation, display, and conclusion drawing. Results. The findings show that Direct Instruction, applied through explicit modeling, repeated guided practice, task segmentation, and positive reinforcement, improved students’ prayer memorization. Improvements were observed in cognitive aspects (accuracy and sequence), affective aspects (motivation and confidence), and psychomotor aspects (clarity of recitation). Conclusion. Direct Instruction is an effective and adaptive approach for inclusive Islamic education, supporting religious learning among students with mild intellectual disabilities and strengthening inclusive pedagogical practices in Islamic educational settings.